High vagally mediated resting-state heart rate variability is associated with superior action cascading. (November 2017) - Colzato, Lorenza S.; Steenbergen, Laura
Abstract: The neurovisceral integration model suggests that individual differences in heart rate variability (HRV), an index of vagal tone, may relate to prefrontal cortical activity and predict performance on cognitive control tasks. The aim of this study was to further verify this model by investigating the relationship between vagally-mediated resting-state HRV and action cascading, a crucial cognitive control function which refers to the ability to cope with multiple response options when confronted with various task goals. Resting-state HRV and performance on the stop-change paradigm, which provides a relatively well-established diagnostic measure of action cascading and response inhibition, was assessed in 88 healthy volunteers (age range 18–33). Compared to individuals with low resting-state HRV, participants with high resting-state HRV showed enhanced action cascading performance, both when a disruption (stopping) and change towards an alternative response were required simultaneously, and when requirements were cascaded (i.e. when the stopping process had already finished at the time the change was required). Our findings represent an important step towards extending our understanding of the neurovisceral integration model in cognitive control. Highlights: Vagally mediated HRV (vmHRV) has a key role in neurovisceral integration model. We investigated the functional relation of resting state vmHRV and action cascading. High resting-state HRV is associated with enhanced action cascading processes. vmHRV might be a novel marker of one's ability to prioritize and cascade different actions.